Estimated Cost And Productivity Of Heavy Equipment Dump Truck On The Blitar / Malang Sp 5 Purwodadi Sta 8 + 450 – 8 + 500 Bts Road Project - Fajar Romadhon; Moch. Zaenuri Arifin; Sony Susanto; Bambang Subiyanto; Titin Widya Risni; Amanda Rodriko Ferijiyansyah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Developments in areas such as roads, buildings, bridges, canals, and other developments are currently developing in the Purwodadi area. One of the jobs, namely the excavation process with a large scale of work, needs to be taken into account in terms of time, cost, and selection of equipment types. During the project, the costs incurred must also be taken into account. This is necessary to complete the work more easily, quickly, and efficiently. Dump trucks are medium to long-distance material transport vehicles. This research aims to determine the dump truck's productivity, the work's budget, and the time required to complete the regular excavation work for STA 8+450 – 8+500 on the BTS BLITAR/MALANG SP 5 PURWODADI road construction project. The research method used is a survey and observation method during the project and calculating the estimated Budget Plan for the rental of heavy equipment Dump Trucks. The results obtained are the number of heavy equipment used in carrying out ordinary excavations and embankments is two units of Dump Trucks with a capacity of 4 m3 with each productivity of 52 m3/hour, which requires 617 cycles to transport material from the excavation area to the stockpile area. Based on the analysis, the estimated cost for the heavy equipment budget for dump trucks is Rp. 5,610.000,00 (Five Million Six Hundred and Ten Thousand Rupiah).